USING MHEALTH TECHNOLOGIES: AN INTEGRATIVE REVIEW OF THEIR IMPACTS ON MATERNAL AND CHILD HEALTH - de Oliveira, Antonia Aparecida Deluca; Stefanes, Luana Cristina; Dunzer, Larissa Gonçalves; Narimatsu, Amanda Kaori; Salles, Jessica Jennifer; Beltrame, Tainá Baldicera; da Cruz, Danielle Cristina Papote; Gonçalves, Bianca Tiellet; de Freitas, Liana Melissa Chaves; Cazagranda, Nicole Smal (Seven Editora, 2025)
The first thousand days of life are a challenging and determinant period for maternal and child health, where good nutrition is essential for the individual's adequate development. Brazil, however, faces challenges such as inequality in access to health services and food insecurity, which negatively impact breastfeeding and infant feeding practices. In this context, mHealth (mobile health) technologies emerge as a promising, innovative, and accessible tool for public health. This review aimed to analyze the efficacy of mHealth in maternal and child nutrition. The research, which included 15 studies primary studies and meta-analysis reviews, demonstrated that mobile health interventions are, for the most part, promising and effective. The evidence points to a positive im-pact, especially concerning breastfeeding practices and the improvement of infant feeding practices. However, the review identified heterogeneity as a cen-tral limitation, with significant variability among the technologies, populations, and outcomes assessed. Despite this, this same diversity reinforces the versa-tility of mHealth. In conclusion, mobile health technologies offer great potential to support essential practices, but they require more rigorous future research and an effort for their egalitarian and equitable integration into public health systems.DOI: https://doi.org/10.56238/sevened2025.037-003